A surprising problem that emerges for humanities academics teaching STEM to communication students - Dawkins, Roger; Naidu, Kate (Journal of Interdisciplinary Studies in Education, 2026)
In this article, researchers examine two humanities teachers’ experiences designing a new interdisciplinary STEM-humanities subject for first-year communication students in Australia. The teachers chose to integrate new disciplinary knowledge themselves. In this article, the researchers use two methodologies to examine the teachers’ experience: (1) a “small data” case study and (2) self-study and post-qualitative dialogic enquiry. Qualitative interview data were collected from the teachers (n = 2) and students (n = 6), and a thematic analysis was conducted. The primary author-researcher—also one of the teachers—reflected on the findings in a first-person narrative account. Emerging from this study are several advantages and challenges of a “dialogic” model of interdisciplinarity in the context of the creative arts.